2018
DOI: 10.1186/s13148-018-0584-y
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation age is not affected in psoriatic skin tissue

Abstract: BackgroundPsoriasis (Ps) is a common chronic inflammatory skin disease. The keratinocytes of psoriatic skin defy normal apoptosis and exhibit active cell proliferation. Aberrant DNA methylation (DNAm) has been suggested relevant through regulating the expression of Ps susceptibility genes. However, it is unclear whether the biological age inferred from DNA methylome is affected.ResultsTo address the above issue, we applied a recently developed methylation clock model to our Chinese Han population dataset, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…[21,22] We identified one prior study demonstrating no significant DNAmAge differences between psoriatic tissues from patients with psoriasis, normal tissues from patients with psoriasis, and normal tissues from healthy control subjects. [12] Given that we replicate this null finding in the present analysis, but report significant findings with SkinBloodAge suggests that methylation metrics intentionally crafted with skin tissues are most sensitive for detecting methylation differences in psoriatic processes. As previously mentioned, SkinBloodAge was developed due to the suboptimal performance of other methylation age metrics in fibroblasts.…”
Section: Con Clus I On S and Per S Pec Tive Ssupporting
confidence: 62%
See 2 more Smart Citations
“…[21,22] We identified one prior study demonstrating no significant DNAmAge differences between psoriatic tissues from patients with psoriasis, normal tissues from patients with psoriasis, and normal tissues from healthy control subjects. [12] Given that we replicate this null finding in the present analysis, but report significant findings with SkinBloodAge suggests that methylation metrics intentionally crafted with skin tissues are most sensitive for detecting methylation differences in psoriatic processes. As previously mentioned, SkinBloodAge was developed due to the suboptimal performance of other methylation age metrics in fibroblasts.…”
Section: Con Clus I On S and Per S Pec Tive Ssupporting
confidence: 62%
“…DNAmAge was evaluated because it was used in a prior psoriasis study. [12] PhenoAge was selected because it is the most robust general methylation predictor of health status described in the literature. [16] GrimAge was selected because it is the most robust methylation predictor of mortality described in the literature.…”
Section: Dna Methylation Data and Dna Methylation Age Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Very little is currently known about the epigenetic age of psoriatic patients. A previous study of DNA methylation age in involved and uninvolved psoriatic skin tissue showed no significant difference [ 21 ]. For our study, we decided to use whole-blood samples instead of skin tissue because psoriasis is no longer considered a simple skin disease.…”
Section: Introductionmentioning
confidence: 98%
“…We included datasets of the same platform to reduce the heterogeneity between different datasets. Only two DNAm datasets were up to the selection criteria, genome-wide DNAm profiling array (GSE115797), containing data from 48 samples with 24 paired tissues (Chandra et al, 2018), and genome-wide DNAm profiling array (GSE73894) including 82 samples with 41 paired tissues (Zhou et al, 2016;Shen et al, 2018), both datasets were generated by the platform GPL13534 (Illumina HumanMethylation450 BeadChip) from the United States.…”
Section: Microarray Data Collectionmentioning
confidence: 99%